PERBANDINGAN FRANCHISE OFFERING CIRCULAR MENURUT PRANATA HUKUM WARALABA DI INDONESIA DAN AUSTRALIA - Isradjuningtias, Agri Chairunisa (Veritas et Justitia, 2020)
Using a comparative law method, this article compares how Indonesian and Australia law on franchise regulates specifically the matter of franchise offering circular.  Hopefully this comparison shall not only indicate similarities or differences in both countries approach but more than that reveals what can be learned from the Australian approach to franchise offering circular.